Analysis of Nonlinear Control Strategies for Quadrotor Stability and Trajectory Tracking - Abiola, Johnson; Ajewole, Oluwafemi; Adewuyi, Philip (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
The quadrotor control as nonlinear and underactuated systems is a huge challenge in getting a fine stabilization and trajectory tracking. The present work seeks to introduce a novel hybrid control structure composed of an Internal Model Control-based Proportional-Integral (IMC-PI) controller, with the integration of a Sliding Mode Controller (SMC) and an Extended State Observer (ESO). The main purpose is to achieve improvement of stability and tracking performance under dynamic flight operations. A six degrees of freedom (6-DoF) dynamic model is developed under rigid body structure and proportional thrust-drag assumptions. An IMC-PI controller is initially employed to stabilize the Euler angles and vertical position but is not able to control the lateral positions (x and y). For this, a hybrid SMC-ESO method is incorporated for enhanced robustness along with precise path tracking. Simulation results reveal that while the stand-alone IMC-PI controller can stabilize altitude and orientation within 3 seconds, it cannot converge to the complete position. Nevertheless, the hybrid controller achieves very precise moving in complex trajectories (helical and figure-eight) within 25 seconds, which outperforms the stand-alone solution. The results confirm the viability of the hybrid controller in autonomous UAV operations where stability and precision are of particular importance.